2023
DOI: 10.1093/oncolo/oyad063
|View full text |Cite
|
Sign up to set email alerts
|

Survival Analysis of 1140 Patients with Biliary Cancer and Benefit from Concurrent Renin-Angiotensin Antagonists, Statins, or Aspirin with Systemic Therapy

Abstract: Background Patients with advanced biliary tract cancers (BTCs) have poor prognoses and limited therapeutic options. Renin-angiotensin antagonists (ACE-I/ARBs), statins, and aspirin may have potential anti-tumorigenic effects and decrease mortality per retrospective analyses in some solid tumors. Objective To evaluate the efficacy of ACE-Is/ARBs, statins, and/or aspirin concurrent to first-line systemic therapy in patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 90 publications
0
2
0
Order By: Relevance
“…This may due to a lower incidence of CCA compared with other cancers, including breast cancer and gastrointestinal cancer. Several studies explored the impact of RASis on patients with advanced, or recurrent, and/or metastatic CCA but got negative results [ 47 , 48 ]. Herein, we described a PS matching cohort of 84 CCA patients and demonstrated that RASis usage could improve the survival of CCA patients.…”
Section: Discussionmentioning
confidence: 99%
“…This may due to a lower incidence of CCA compared with other cancers, including breast cancer and gastrointestinal cancer. Several studies explored the impact of RASis on patients with advanced, or recurrent, and/or metastatic CCA but got negative results [ 47 , 48 ]. Herein, we described a PS matching cohort of 84 CCA patients and demonstrated that RASis usage could improve the survival of CCA patients.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, a recently published study that included 1140 biliary cancer patients evaluated the benefit of concurrent statins with systemic therapy. Patients who received concomitant statins with systemic therapy versus those who received only systemic therapy did not experience improved progression-free (5.5 vs. 5.5 months; hazard ratio (HR) 1.1; p = 0.51) or overall survival (12.3 vs. 12.6 months; HR 1.1; p = 0.18), respectively [159].…”
Section: Statins In Cca Treatmentmentioning
confidence: 92%